STRATEGI PENGAWASAN TERHADAP UJARAN KEBENCIAN DI MEDIA SOSIAL PADA PEMILU - Dewi Anggraeni; Adrinoviarini Adrinoviarini (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2020)
The political year is a fertile vehicle for disseminating news of hate speech, forms of intolerance, and false information (hoaxes) decorating the Indonesian social media universe. Election campaigns provide fertile ground for hate speech and incitement, especially on social media. This research aims to analyze and identify the prevalence of hate speech in the DKI Jakarta gubernatorial election by evaluating the regulations regarding hate speech on social media according to stakeholders and appropriate and effective strategies in preventing and taking action against hate speech violations in the Pilkada/Election. This type of research is descriptive qualitative, which portrays the phenomenon of the DKI Jakarta governor election in 2017, The data collection technique used was a focus group discussion by inviting several sources. The results of this study reveal that; Hate speech in 2017 on social media, especially Facebook, has increased in the momentum of the Pilkada. The ITE Law and SE / 06 / X / 2015 have been implemented by various stakeholders as an effort to prevent and prosecute hate speech offenders, although this has not been maximized due to the weak media literacy of Indonesian society itself. The case for the 2017 DKI Jakarta election as a prototype for the National Election. Therefore, election organizers need to pay special attention to monitoring social media during the election period.